Transportation of Passengers as Public Administration Object - Меlnychenko Oleksandr; Dunayev, Ihor (Theory and Practice of Public Administration, 2019)
The intensi cation of human life stipulates the growing needs of the population for short- and long-distance transportation. Such needs arise in a majority of the population, and to a large extent they are satis ed through the use of different modes of public transport. Taking into consideration the social signi cance thereof, as well as their inability to reconcile the interests of passengers and transport operators, passenger transportation should become an object of public administration. The above-said explains the topicality of the present research. Public administration agents focus their attention on continuous control and rather a strict regulation of the activity of passenger transportation operators. In such a case, the state retains the authority of resolving most of the issues related to passenger transportation development. The conducted summation of the content of the author’s abstracts of the defended theses and publications in specialized editions made it possible to specify within the scope of the recognized methods (administrative, economic, normative, organizational, and socio-psychological) of the regulatory impact and the range of means of public administration of passenger transportation. Passenger transportation is of great social and economic importance, which makes it an object of public administration. A proper methodological support for that process, the upgraded classi cation of mechanisms (which are distinct in such features as form, manner, object, and impact directionality), and a speci ed (within the recognized methods of regulatory impact) list of means for public administration of passenger transportation should shape the prerequisites for further enhancement of that impact effectiveness. Systematization of the problems (administrative and legal, economic, material and technical, organizational, and socio-psychological) in the researched domain is the baseline for the task of discerning priority areas for implementation of the mechanisms for public administration of the passenger transportation in Ukraine. Further scientic surveys will be devoted to elaboration of recommendations aimed at improvement of quality of passenger transportation and development of transport enterprises.